2009
DOI: 10.1086/606056
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Evaluation of Rifabutin in Combination with Lopinavir‐Ritonavir in Patients with HIV Infection and Active Tuberculosis

Abstract: The recommended rifabutin doses for use with lopinavir-ritonavir may be inadequate in many patients. Monitoring of plasma concentrations is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 16 publications
2
64
1
Order By: Relevance
“…As this was an explorative, crossover trial, no formal sample size calculations were performed. However, a minimum of at least 13 volunteers completing all sessions was considered sufficient to allow for relevant conclusions (5,12,17,20,22). With this number of volunteers and the expected within-subject variation on the logarithmic scale of 0.035 in AUC from time point zero up to the time point of the last quantifiable concentration (AUC last ) for DRV, the range of the 90% confidence interval (CI) of the ratio was estimated to be from Ϫ12.3% to ϩ14.0%.…”
Section: Methodsmentioning
confidence: 99%
“…As this was an explorative, crossover trial, no formal sample size calculations were performed. However, a minimum of at least 13 volunteers completing all sessions was considered sufficient to allow for relevant conclusions (5,12,17,20,22). With this number of volunteers and the expected within-subject variation on the logarithmic scale of 0.035 in AUC from time point zero up to the time point of the last quantifiable concentration (AUC last ) for DRV, the range of the 90% confidence interval (CI) of the ratio was estimated to be from Ϫ12.3% to ϩ14.0%.…”
Section: Methodsmentioning
confidence: 99%
“…Subtherapeutic levels of rifabutin have been associated with the development of acquired rifamycin resistance (257). This is illustrated by case reports of the development of TB relapse due to acquired rifampin resistance after treatment with everyother-day rifabutin and ritonavir-boosted PI-based ART (28,134). There remains a critical need to better understand the pharmacokinetic interactions between rifabutin and protease inhibitors in HIV-infected patients.…”
Section: Rifabutin Can Be Used With Protease Inhibitorsmentioning
confidence: 99%
“…There remains a critical need to better understand the pharmacokinetic interactions between rifabutin and protease inhibitors in HIV-infected patients. Rifabutin drug concentration monitoring may be warranted during treatment when it is feasible (28).…”
Section: Rifabutin Can Be Used With Protease Inhibitorsmentioning
confidence: 99%
“…A pharmacokinetic study by Boulanger et al measured the drug concentrations of rifabutin and lopinavir-ritonavir as well as the rifabutin metabolite, 25-desacetyl rifabutin, in HIV positive patients with active tuberculosis. (Boulanger et al, 2009) When rifabutin was administered at 150 mg thrice weekly in combination with lopinavir-ritonavir a majority of the patients had C max values below the normal range (0.3 to 0.9 ug/ml). PK-PD simulations by the authors suggested that when the two medications are administered together, rifabutin should be given daily, and that doses as high as 450 mg daily would be needed to achieve free drug plasma concentrations at or above the minimum inhibitory concentration (MIC) for part of the dosing interval.…”
Section: Rifabutin and The Pismentioning
confidence: 98%